About foliations and differential forms - Jurado Cerrón, Liliana Olga (2020)
In this work we aim to study the foliations of arbitrary codimension related to the differential forms, obtaining two main results. In the first result we showed that from a foliation of codimension q in Cn one can obtain a foliation in CPn. The second result shows the characterization of the transversely affine foliations of arbitrary codimension in terms of matrices.